Tahap Kepuasan Guru Terhadap Pentaksiran Berasaskan Sekolah (PBS) Bagi Mata Pelajaran Kemahiran Hidup Bersepadu Di Sekolah Menegah Harian Biasa Di Sarawak - Sern, Lai Chee; Chee, Chong Siaw (Online Journal for TVET Practitioners, 2018)
This research was conducted to investigate the satisfaction level towards School Based Assessment (SBA) among teachers who teach the subject of Integrated Living Skills at Secondary School in Sarawak. This research employed survey design in which questionnaire was used as research instrument. A total of 242 school teachers who teach Integrated Living Skills subject at Secondary School in five different districts within Sarawak were selected to participate in this research. The collected data was analysed using descriptive statistics. In general, the research findings revealed that the teachers’ satisfaction towards SBA implementation was at a moderate level. In specific, teachers were highly satisfied with the effectiveness of training and courses. However, the teachers perceived that the SBA has substantially increased teachers’ workload. In terms of students’ mastery of contents and school administrator’s monitoring, the results indicated that the teachers were moderately satisfised. The outcomes of this research are expected to be used as a reference to assist relevant quarters to improve the SBA implementation, and thereby contributing to effectiveness of Malaysia Education System.